Implementation of Murabahah Contracts in Buying and Selling Housing - Audria, Nivia Mina; Adinugraha, Hendri Hermawan (Program Study Islamic Banking, Faculty of Economics and Bussiness Islam, State Islamic Institute of Manado (IAIN) Manado, 2021)
Indonesia's economic development related to the demand for housing is increasing. Many indicators can be seen in the community, such as the number of community housing developments. These developments create property business opportunities such as buying and selling housing, especially those that avoid the element of usury so that they look for a sharia buying and selling process, one of which is a murabahah contract. This study aims to determine the implementation of the murabahah contract in buying and selling housing. This research is a descriptive research research based on literature study. Data collection is done by taking from literature sources that are relevant to the research problem. Based on the analysis of various literatures, this study concludes that in the implementation of buying and selling murabahah contracts, it is required that both parties must know the benefits that have been agreed upon and the element of usury is prohibited. In its implementation, it must meet the pillars and conditions according to sharia principles. Traded goods are not included in the categories prohibited by Islamic law. But there are some in the implementation of the murabahah contract, there are some that have been modified related to the murabahah contract.